Workload evaluation of clinical pharmacists in the ambulatory care setting. Issue 6 (28th April 2020) - Van Dril, Elizabeth; Schumacher, Christine; Kliethermes, Mary Ann; Borchert, Jill S.; Buros Stein, Amy
Abstract: Introduction: Inpatient clinical pharmacists' roles and contributions to team‐based care are well established; however, there is limited evidence describing the activities and processes for the delivery of care by ambulatory care clinical pharmacists. Objectives: The primary objective was to measure time spent on daily activities that comprise the workload of clinical pharmacists providing direct patient care services in an integrated ambulatory care setting. Methods: A prospective, ethnographic, and observational pilot study was conducted at six pharmacist‐integrated multidisciplinary ambulatory care clinics. Clinical pharmacist participants were observed for up to three nonconsecutive clinic workdays. Participant demographics, site characteristics, and self‐reported engagement in direct patient care activities were collected. Workload was evaluated through direct observation of time spent on daily clinical and administrative activities. Time allocated, visit type, number of disease states assessed, and use of clinical support staff were collected for each visit. Results were stratified based on participant engagement in targeted, dual, or comprehensive medication management (CMM) visits, in which one, two, or three or more disease states were assessed, respectively. The primary outcome was analyzed using descriptive statistics. Results: Ten clinical pharmacists were observed for a total of 26 clinic workdays. Of prespecified activities, clinical pharmacist participants spent the most time documenting care activities, spending a mean (SD) of 6.6 (6.7), 8.0 (8.2), and 7.6 (7.7) minutes after targeted, dual, and CMM visits, respectively. There was a large variation in the distribution of prespecified clinical and administrative activities among participants. Years of practice experience, postgraduate training, board certification(s), duration of practice at the site, and site characteristics did not affect the distribution of time spent on activities ( P  > .05). Conclusions: This evaluation articulates the daily activities that contribute to the work of ambulatory care clinical pharmacists and may serve as the foundation to perform more comprehensive evaluations of their contributions to patient outcomes.